Distribution Pattern of Coffee Berry Borer (Hypothenemus Hampei) on Arabica and Robusta Coffee - Soekadar Wiryadiputra (Indonesian Coffee and Cocoa Research Institute, 2014)
Coffee berry borer [CBB, Hypothenemus hampei (Ferr.)] is the main pest on coffee causing a significant losses. Distribution pattern of the pest is not known deeply until now, especially in Indonesia. The data of distribution pattern of pest is very important in constructing the strategy of integrated pest management, especially to determine a sampling method for monitoring of the pest. This experiment aimed to reveal the distribution pattern of CBB both spatially and vertically. The experiment was conducted on Arabica and Robusta coffee, located in Kalibendo estate in Banyuwangi East Java. A plot with 400 (20 x 20) of coffee trees were observed for infestation and population of CBB, at four branches on south, north, east and west directions for each tree. Collected data were analyzed to obtain the value of mean, variance (=s2), variance/mean relationship (=I), index of Morisita (=Iδ), coefficient of Green (=Cx) and k exponent of Negative Binomial. Results of the experiment revealed that spatial distribution pattern of CBB, both on Arabica an Robusta coffee, as well as for infestation and population parameters, was fit with aggregated or clumped distribution. For vertical distribution, it inclined that CBB infestation and population in the lower part of coffee tree was higher than in central and upper part of coffee tree. Plenty of infested coffee berries leaved on soil surface may result in higher infestation and population in the lower part.Key words: Arabica coffee, Robusta coffee, Hypothenemus hampei, spatial distribution, vertical distribution.